Modern Physics As A New Step In Dialogue Of Man With Nature - Voronov, Vladimir Kirillivich (Advances in Social Sciences Research Journal, 2017)
The paper describes the content of a set of textbooks entitled "Modern Physics" consisting of three monographs, which cover the main advancements of physics approximately for last fifty – sixty years (since the middle of the twentieth century). The first textbook contains ten chapters. The second book includes five chapters. In the third book, consisting of three parts, physical foundations of nanotechnologies are discussed. The textbooks are written on the basis of the material, which is selected from various sources (reviews, monographs). The authors mainly discuss the papers published in "Advancements of physical sciences" journal. The total volume of three books is about eighty printed pages. Justification of the significance of the work is also provided. In this line, it is noted that rapid growth of scientific information and ever-strengthening integration of various branches of science lead to the problems of methodological character, which solution is connected with publication of course books. It is also underlined that since the middle of the twentieth century, a number of new branches of physics, including the nonlinear optics, physics of open systems, quantum information, molecular structure and dynamics, has been developed. There is rather extensive scientific literature related to branches of physics. These are mainly original papers and reviews published in specialized journals. However, as a rule, this literature is intended for experts. As for training materials, they are almost absent. Keywords: modern physics; condensed state; nanomaterials.